Strategic planning: A chance for spatial innovation and creativity. - Kunzmann, Klaus R. (Routledge, 2013)
Strategische Planung: Eine Chance für Raum, Innovation und Kreativität. - Der Autor geht auf die Hoffnungen der Planergemeinde ein, die mit dem Begriff der strategischen Planung verbunden sind und die sich vor allem auf die Überwindung der Schranken traditioneller Planung wie etwa der Flächennutzungsplanung richtet; er benennt dabei die Hauptursachen des bisherigen Scheiterns. Aber auch die strategische Planung ist nicht vor Missverständnissen und unrealistichen Erwartungen gefeit, wie der Beitrag zeigt. Schließlich werden aber die kreativen und innovativen Potenziale der strategischen Planung benannt: die Einbeziehung innovativer Elemente in bestehende Raumentwicklungsprozesse, die strategische Planung selbst als innovatives Planungsmodell, die Offenheit und Flexibilität des Prozesse, die Eröffnung neuer Perspektiven und die Einbeziehung planungsferner Stakeholders, die Förderung der lokalen und regionalen Wirtschaft.

Strategic planning has become the new hope of the community of academic planners in Europe as a means to overcome the shortcomings of traditional land use planning at the local and regional levels of planning and decision-making. To a realistic assessment of the potential of strategic planning in practice one should recall, why, as a rule, traditional land use planning failed: land use planners neglect the economic dimensions, the nature of the land use planning has been largely misunderstood; the public sector didn't have the means to pro-actively develop urban expansion; cities expanded into city regions without any adjustment of administrative boundaries. The innovative and creative dimensions of strategic spatial planning are: strategic planning brings innovative elements into ongoing spatial development processes, strategic planning is an innovative and creative process in itself, is an open and flexible process, strategic planning creates new windows of opportunity; the process of strategic planning can better prepare the ground for promoting innovative urban and regional processes.
Keywords: Planungstheorie; Raumplanung; Planungspraxis; Planungsprozess; Flächennutzungsplanung; Innovation; Strategische Planung; Planungsinstrument; Kreativität